Real-time Business Process Intelligence. Comparison of different architectural approaches using the example of the order-to-cash process. - Korotina, Anastasiia; Müller, Oliver; Debortoli, Stefan (International Conference on Wirtschaftsinformatik)
Business operations are becoming more and more integrated with the real-time intelligence. Core business activities are being carried out through OLTP systems that provide limited monitoring capabilities of the running process instances. The article shows how to turn the gap between the classic transactional system and the process-centric approach into an organization that provides more accurate and faster decisions on the strategic and operational management levels. This study aims at determination of what kind of information can be retrieved during the process execution and it tries to identify the need for the real-time process intelligence on the example of the order-to-cash process. Furthermore, we compare two architectural approaches of the real-time process intelligence monitoring system. The proposed frameworks retrieve process data from the ERP system in order to record crucial performance indicators on a real-time basis with the use of the in-memory technology.

Determinants of loan securitization in European banking - Farruggio, Christian; Uhde, André (Journal of Banking and Finance)
Analyzing 75 securitizing and non-securitizing stock-listed banks in the EU-13 plus Switzerland over the period from 1997 to 2010, this paper provides empirical evidence that loan securitization in Europe is a composite decision based on bank-specific as well as market- and country-specific determinants. In addition, we find that these determinants remarkably change when separately investigating securitization transactions during the pre-crisis and crisis period. Moreover, results from several subsample regressions reveal that determinants of loan securitizations in Europe depend on the transaction type, the underlying asset portfolio and the regulatory and institutional environment under which banks operate.
Keywords: Securitization; Determinants; European banking

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

Cross-cutting organizational and demographic divides and the performance of research and development teams: two wrongs can make a right - Iseke, Anja; Kocks, Birgit; Schneider, Martin; Schulze-Bentrop, Conrad (R&D Management)

Testing vs. building accounting theory with experimental research: insights from management research - Reimsbach, Daniel; Hauschild, Bastian (International Journal of Behavioural Accounting and Finance)
Keywords: Geology; Ocean Engineering; Water Science and Technology

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung. - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Analyse der Anwendbarkeit von Six Sigma als Instrument der Investitionsplanung - Heitmann, Ingmar (Ausgewählte Probleme des Logistikmanagements)

Konzeption eines Logistikcontrollingansatzes zur Abwicklung zeitkritischer Transportvorgänge - Puls, Christoph (Ausgewählte Probleme des Logistikmanagements)

Entwicklung eines qualitativen Verfahrens zur Bewertung logistischer Investitionen - Koch, Christian (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Opitz, Oliver (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Faupel, Christian (Ausgewählte Probleme des Logistikmanagements)

Managing the Bright and Dark Sides of Status Endowment in Hierarchical Loyalty Programs - Eggert, A.; Steinhoff, Lena; Garnefeld, I. (Journal of Service Research)

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

EU-StORe- Creating European Standards for Open Education and Open Learning Resources - Schneider, Jennifer Nicole

Research on didactical material and open learning resources - Schneider, Jennifer Nicole

Training Courses and Implementation - Schneider, Jennifer Nicole

The EU-StORe-Survey - Schneider, Jennifer Nicole

Evaluation of the first Prototype version of AGnovel - Schneider, Jennifer Nicole

Evaluation - Schneider, Jennifer Nicole

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience